Social Sciences E-Module Contains Balinese Folk Stories Based on Pancasila Student Profiles for Third Grade of Elementary School - Putri, Kadek Dea Krisna; Wulandari, I Gusti Agung Ayu (Jurnal Pendidikan Multikultural Indonesia, 2024)
Students in elementary schools tend to be passive in their learning and there is a lack of use of various learning media in the learning process, this causes students to feel less interested and have difficulty understanding the material. The aim of this research is to develop learning media in the form of a social studies e-module containing Balinese folklore based on Pancasila student profiles. The development model used in this research is the Dick and Carey development model. Data collection methods were carried out by observation, interviews, questionnaires, and tests. The subjects in this study consisted of 4 experts and 64 third grade students in elementary schools. Data were analyzed using inferential statistical techniques. The results obtained from the learning content expert test assessment were 96.15% (very good), the learning design expert test assessment was 100% (very good), the learning language expert test assessment was 80% (very good), the learning media expert test assessment of 95% (very good), individual trial assessment of 92.5% (very good), and small group trial assessment of 91.66% (very good). Based on the effectiveness test results, the tcount value was greater than the ttable (9,145 more than 1,999). Thus, it can be concluded that the development of a social studies e-module containing Balinese folklore based on the Pancasila student profile is effectively applied to the social studies content of third grade of elementary school.